Profit Loss Sharing (PLS) and Its Implementation in Indonesian Islamic Banking - Muhammad Anwar Fathoni; Suryani Suryani (IQTISHODUNA: Jurnal Ekonomi Islam, 2020)
Writing this article aims to determine the concept of Profit Loss Sharing (PLS) and its implementation in Indonesian Islamic banking. The data used in this article is sourced from secondary data from books, scientific journals, sharia banking statistical data released by the Financial Services Authority (OJK) and other sources relevant to the focus of the discussion. The author finds that the application of the concept of profit loss sharing in mixing agreements is the antithesis of the concept of interest which has dominated the banking world. However, in practice, not all Islamic banking applies this concept. Even Islamic banking in Indonesia is more likely to choose revenue sharing to safeguard the interests of its customers. The author only uses secondary data to measure the implementation of PLS in Islamic banking, so that further research will be better if conducting primary data mining to get a broader picture related to the theme of the article.